Feminist Voice in Abhi Subedi’s Agniko Katha - Mishra, Indira Acharya (Researcher: A Research Journal of Culture and Society, 2020)
This article analyzes Abhi Subedi's play, Agniko Katha, from a feminist perspective. Feminist critics blame that the classics of literature are partly responsible for creating and perpetuating the myth about 'eternal feminine.' They claim that there are only two images available for women in patriarchal literature. One is the image of a virtuous passive woman and the other is the promiscuous selfish woman. The author of such literary texts rewards the virtuous woman whereas they punish the promiscuous one. Feminists argue that the underlying message of this method is: if a woman wants to survive in patriarchy she must act feminine. This effects women in their real life situation for they tend to perform feminine gender roles though they are disadvantageous to them. Thus, they protest the stereotype depiction of female characters in literary and other cultural texts. The article argues that Subedi defies the traditional notion of femininity and creates new roles for his female characters. The protagonist of the play denies to play her assigned feminine role and searches for a new role for her. She questions and protests the patriarchal gender roles which are bias against women. Thus, it is relevant to explore the feminist voice in the text. The finding of the article suggests that women, too, have the potentiality to create new roles for themselves and bring change into society.